SOSIALISASI INTENTER DALAM MEMBANGUN GENERASI REMAJA CERDAS DIGITAL DI MTS BAITUL MUTTAQIN - Marlina Putri Nurfatin (Nawasena Bhakti, 2025)
The rapid development of digital technology has a major impact on the lives of young people, especially related to interactions on social platforms and the use of information technology. The socialization activity “Building a Generation of Digitally Smart Teenagers” held at MTs Baitul Muttaqin aims to improve digital literacy and increase adolescent awareness of digital ethics, the dangers of fake news, and the importance of protecting personal data. This activity was held with a participatory and educational approach that included the delivery of materials, discussions, interactive quizzes, and reflections. The results of the socialization activity showed that the participants showed an increased understanding of the use of digital media that is appropriate, polite, and responsible. They also became more aware of the risks inherent in social media, such as cyberbullying and the spread of incorrect information. With an interactive and fun approach, this program succeeded in having a positive influence in shaping the digital character of teenagers who are critical, ethical, and ready to face the challenges of cyberspace in a healthy and productive way.